Hydrophobic Tagged Dihydrofolate Reductase for Creating Misfolded Glycoprotein Mimetics. (25th January 2016) - Hachisu, Masakazu; Seko, Akira; Daikoku, Shusaku; Takeda, Yoichi; Sakono, Masafumi; Ito, Yukishige
Abstract: In the endoplasmic reticulum (ER), nascent glycoproteins that have not acquired the native conformation are either repaired or sorted for degradation by specific quality‐control systems composed by various proteins. Among them, UDP‐glucose:glycoprotein glucosyltransferase (UGGT) serves as a folding sensor in the ER. However, the molecular mechanism of its recognition remains obscure. This study used pseudo‐misfolded glycoproteins, comprising a modified dihydrofolate reductase with artificial pyrene–cysteine moiety on the protein surface (pDHFR) and Man9 GlcNAc2 ‐methotrexate (M9‐MTX). All five M9‐MTX/pDHFR complexes, with a pyrene group at different positions, were found to be good substrates of UGGT, irrespective of the site of pyrene modification. These results suggest UGGT's mode of substrate recognition is fuzzy, thus allowing various glycoproteins to be accommodated in the folding cycle. Abstract : Pseudo‐misfold glycoprotein : In the endoplasmic reticulum, UGGT recognizes misfolded glycoproteins and transfers a glucose residue to the non‐reducing ends of high‐mannose‐type glycans. The mechanism by which UGGT senses the folding status has not been understood. To address this, pseudo‐misfolded glycoproteins were designed and chemically synthesized.